(untitled) (CIPEEX, 2025)
Intimate plastic surgery is a specialized field within aesthetic surgery that aims to improve the physical and psychological well-being of patients by addressing concerns related to genital appearance and function. Procedures such as labiaplasty, vaginoplasty, and clitoral hood reduction are sought by patients for both cosmetic and functional reasons. These surgeries can have significant effects on patients’ sexual satisfaction and overall quality of life. However, despite their growing popularity, there is still much to be explored regarding the impact of these procedures on sexual function. OBJECTIVE: This study aims to analyze recent research that evaluates the relationship between intimate plastic surgery and sexual satisfaction. The goal is to understand the extent to which these surgeries interfere with or enhance sexual experience and to provide insights into the factors that contribute to patient satisfaction. METHOD: An integrative literature review was conducted using articles from databases such as PubMed, Scielo, and Google Scholar. Keywords used in the search included "intimate plastic surgery," "sexual satisfaction," "labiaplasty," and "vaginoplasty," covering studies published from 2015 to 2023. RESULTS: The studies reviewed indicate that most patients undergoing intimate plastic surgery report improved sexual satisfaction and body image. However, the level of satisfaction can vary depending on the type of surgery and the individual characteristics of the patient. Complications are relatively rare but can impact the overall outcome, particularly in cases of improper surgical techniques or unrealistic patient expectations. Additionally, the psychological impact of these surgeries is an area that requires further investigation. CONCLUSION: Intimate plastic surgery has been shown to positively impact the sexual lives of many patients, but it is crucial to properly assess the needs and expectations of each individual. While the procedures offer aesthetic and functional benefits, informed consent and a thorough discussion of risks and outcomes are essential to ensure patient satisfaction and well-being.